Understanding of Reward Prize Hadiths In Indonesia (Comparative Study of the Ahmad Hassan and Siradjuddin Abbas Methods) - Rozian Karnedi; Dudung Abdurahman; Muhammad Alfatih Suryadilaga (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article explored the differences between Ahmad Hassan and Siradjuddin Abbas understanding on reward prize hadith, the methods used and the factors influencing differences. As a cadre of the two competing groups, these two scholars formulated an understanding of the reward of hadith to legitimize the understanding of each group.The results of the study found that Ahmad Hassan viewed that reward prize hadith contrary to al-Qur’an and rejected all methods of resolution. So this hadithwas a da’if quality and Mardud status. Besides, Siradjuddin Abbas looked at the reward prize hadith wasṣaḥiḥ quality and maqbūl status using a correlative approach. Understanding rewards prize hadith by Ahmad Hassan and Siradjuddin Abbas disputed of religious understanding between the Young People and the Old People and influenced the socio-cultural context of the mid-XX century